2021
DOI: 10.1093/mnras/stab2082
|View full text |Cite
|
Sign up to set email alerts
|

A survey for variable young stars with small telescopes – IV. Rotation periods of YSOs in IC 5070

Abstract: Studying rotational variability of young stars is enabling us to investigate a multitude of properties of young star-disc systems. We utilize high cadence, multiwavelength optical time series data from the Hunting Outbursting Young Stars citizen science project to identify periodic variables in the Pelican Nebula (IC 5070). A double blind study using nine different period-finding algorithms was conducted and a sample of 59 periodic variables was identified. We find that a combination of four period finding alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In order to test the quality of our derived periods, we compared them to the periods published in Bhardwaj et al (2019) and Froebrich et al (2021). Both papers considered objects in the Pelican Nebula region (see Figure 1).…”
Section: Period Recovery For Strictly Periodic Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to test the quality of our derived periods, we compared them to the periods published in Bhardwaj et al (2019) and Froebrich et al (2021). Both papers considered objects in the Pelican Nebula region (see Figure 1).…”
Section: Period Recovery For Strictly Periodic Variablesmentioning
confidence: 99%
“…Of the 40 periodic variables identified in Froebrich et al (2021), 32 are within 2″ of a source in our sample, of which 20 we classify as periodic in Q − M space. All 20 have periods within 5% of our derived periods.…”
Section: Period Recovery For Strictly Periodic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The project Hunting Outbursting Young Stars (HOYS) is one of the endeavours designed to overcome this deficit, by collecting observations from a multitude of small telescopes from professional and amateur observatories, all using a pre-defined observing strategy and a specific set of target regions (see overview paper by Froebrich et al 2018). In the first HOYS papers we have, for example, presented a study of rotation in one star forming region (Froebrich et al 2021), a follow-up study of spot properties in the same region (Herbert et al 2023), and an analysis of the variability in a specific source that is caused by eclipses from structures in a protoplanetary disk (Evitts et al 2020), among other findings. In this paper we take a more holistic view -we aim to select prospective young stars in all 25 HOYS target regions, using data from Gaia, collate information about these samples, and study general variability properties among those samples.…”
Section: Introductionmentioning
confidence: 99%
“…The results of long-term photometric monitoring observations of the region have been reported by Poljančić et al (2014), Ibryamov et al (2015), and Ibryamov et al (2018), providing detailed analyses of small samples of stars based on decades of multi-color data from numerous observatories. Bhardwaj et al (2019) found 56 periodic variables in the Pelican Nebula region, visually classifying an additional 11 variables as non-periodic while Froebrich et al (2021) identified 59 periodic variables, many of which overlap the Bhardwaj et al (2019) sample.…”
Section: Introductionmentioning
confidence: 99%